Quality of Cosmetic Argan Oil Extracted by Supercritical Fluid Extraction from Argania spinosa L. - Chouaa Taribak; Lourdes Casas; Casimiro Mantell; Zoubaida Elfadli; Rédouane E. Metni; Enrique J. Martínez de la Ossa (Journal of Chemistry)
Argan oil has been extracted using supercritical CO2. The influence of the variables pressure (100, 200, 300, and 400 bar) and temperature (35, 45, 55°C) was investigated. The best extraction yields were achieved at a temperature of 45°C and a pressure of 400 bar. The argan oil extracts were characterized in terms of acid, peroxide and iodine values, total tocopherol, carotene, and fatty acids content. Significant compositional differences were not observed between the oil samples obtained using different pressures and temperatures. The antioxidant capacity of the argan oil samples was high in comparison to those of walnut, almond, hazelnut, and peanut oils and comparable to that of pistachio oil. The physicochemical parameters of the extracted oils obtained by SFE, Soxhlet, and traditional methods are comparable. The technique used for oil processing does not therefore markedly alter the quality of argan oil.